Optimising the impact of health services research on the organisation and delivery of health services: a mixed-methods study - Martin Marshall; Huw Davies; Vicky Ward; Justin Waring; Naomi J Fulop; Liz Mear; Breid O'Brien; Richard Parnell; Katherine Kirk; Benet Reid; Tricia Tooman (NIHR Journals Library, 2022)
Background: The limitations of 'knowledge transfer' are increasingly recognised, with growing interest in 'knowledge co-production in context'. One way of achieving the latter is by 'embedding' researchers in health service settings, yet how to deliver such schemes successfully is poorly understood. Objectives: The objectives were to examine the nature of 'embedded knowledge co-production' and explore how embedded research initiatives can be designed more effectively. Design: The study used four linked workstreams. Workstream 1 involved two parallel literature reviews to examine how 'knowledge co-production' and 'embedded research' are conceptualised, operationalised and discussed. In workstream 2, a scoping review of exisiting or recent 'embedded researcher' schemes in UK health settings was carried out. Workstream 3 involved developing four in-depth case studies on such schemes to understand their mechanisms, effectiveness and challenges. In workstream 4, insights from the other workstreams were used to provide recommendations, guidance and templates for the different ways embedded co-production may be framed and specified. The overall goal was to help those interested in developing and using such approaches to understand and address the design choices they face. Setting: Embedded research initiatives in UK health settings. Data sources: Data were sourced from the following: analysis of the published and grey literature (87 source articles on knowledge co-production, and 47 published reports on extant embedded research initiatives), documentation and interviews with key actors across 45 established embedded research initiatives, in-depth interviews and site observations with 31 participants over 12 months in four intensive case studies, and informal and creative engagement in workshops (n = 2) and with participants in embedded research initiatives who joined various managed discussion forums. Participants: The participants were stakeholders and participants in embedded research initiatives. Results: The literature reviews from workstream 1 produced practical frameworks for understanding knowledge co-production and embedded research initiatives, which, with the scoping review (workstream 2), informed the identification and articulation of 10 design concerns under three overarching categories: intent (covering outcomes and power dynamics), structures (scale, involvement, proximity and belonging) and processes (the functional activities, skills and expertise required, nature of the relational roles, and the learning mechanisms employed). Current instances of embedded research were diverse across many of these domains. The four case studies (workstream 3) added insights into scheme dynamics and life cycles, deepening understanding of the overarching categories and showing the contingencies experienced in co-producing knowledge. A key finding is that there was often a greater emphasis on embeddedness per se than on co-production, which can be hard to discern. Finally, the engaging and influencing activities running throughout (workstream 4) allowed these research-rooted insights to be translated into practical tools and resources, evidenced by peer-reviewed publications, for those interested in exploring and developing the approach. Conclusions: Embedded research has a strong underpinning rationale, and more is becoming known about its design and management challenges. The tools and resources developed in this project provide a coherent evidence-informed framework for designing, operationalising and managing such schemes. It cannot yet be said with clarity that the potential benefits of embedded research are always deliverable, nor what the cost would be. Future work: With the means to describe and categorise different types of embedded research initiatives, more evaluative work is now needed to examine the relative merits and costs of different designs. Funding: This project was funded by the National Institute for Health Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 3. See the NIHR Journals Library website for further project information.